An Online Survey of Science Educators’ Challenges of Implementing Digital Pedagogy in Public Universities in Kogi State, Nigeria - Ajayi, Victor Oluwatosin; Ameh, Rachael Folake; Penda, Bibiana Mwuese (Journal of Multidisciplinary Research and Development, 2026)
This study explored an online survey of science educators’ challenges of implementing digital pedagogy in public universities in Kogi State, Nigeria. The population of this study consists of 52 science educators in the four public universities in Kogi State, Nigeria. There was no sampling since the population was manageable. The study adopted a descriptive survey research design. An online google form survey questionnaire titled Challenges of Implementing Digital Pedagogy Questionnaire (CIDPQ) was the instrument used for data collection. CIDPQ was trial tested which yielded a reliability value of 0.88 using Cronbach Alpha. The CIDPQ contained 22-items. Two research questions and two null hypotheses guided the study. The research questions were answered using mean and standard deviation scores while the null hypotheses were tested at 0.05 level of significance using t-test statistics. The study revealed that there is no significant difference between the mean ratings of male and female science educators on challenges of implementing digital pedagogy (t=1.89, df=50, P>0.05). There was no significant difference between the mean ratings of male and female science educators on measures that could address the challenges of implementing digital pedagogy (t=1.76, df=50, P>0.05). Thus, there is need for universities administrators and other relevant educational stakeholders to provide sufficient and accessible ICT resources and also provide continuous professional development on how to effectively implement digital pedagogy